Back to the Future: The Digital Millennium Copyright Act and the Trans-Pacific Partnership - Matthew Rimmer (Laws, 2017)
The Trans-Pacific Partnership (TPP) is a trade agreement, which seeks to regulate copyright law, intermediary liability, and technological protection measures. The United States Government under President Barack Obama sought to export key features of the Digital Millennium Copyright Act 1998 (US) (DMCA). Drawing upon the work of Joseph Stiglitz, this paper expresses concerns that the TPP would entrench DMCA measures into the laws of a dozen Pacific Rim countries. This study examines four key jurisdictions—the United States, Canada, Australia, and New Zealand—participating in the TPP. This paper has three main parts. Part 2 focuses upon the takedown-and-notice scheme, safe harbours, and intermediary liability under the TPP. Elements of the safe harbours regime in the DMCA have been embedded into the international agreement. Part 3 examines technological protection measures—especially in light of a constitutional challenge to the DMCA. Part 4 looks briefly at electronic rights management. This paper concludes that the model of the DMCA is unsuitable for a template for copyright protection in the Pacific Rim in international trade agreements. It contends that our future copyright laws need to be responsive to new technological developments in the digital age—such as Big Data, cloud computing, search engines, and social media. There is also a need to resolve the complex interactions between intellectual property, electronic commerce, and investor-state dispute settlement in trade agreements.